« Dans la souffrance, parler et consentir » : L’écriture et le mouvement de Job 3 (Hekima Review, 2008)
After the painful events he received, when the friends come to see him, Job, first, opens the discussion. His first monologue apparently takes the form of malediction, and this form will change slowly to that of the supplication in the Psalms. Job engages in a severe critique of the received theology of Israel. He struggles against his imagination, which tells him to rapidly put an end to the situation. But, actually, Job has begun to talk: when he finishes his first speech, he gives his consent to what is going to happen.